Політична толерантність як імператив процесу забезпечення соціально-політичної стабільності - Іванова, Анастасія В’ячеславівна; Иванова, Анастасия Вячеславовна; Ivanova, Anastasiia V. (Одеса, 2019)
Дисертація на здобуття наукового ступеня кандидата політичних наук за спеціальністю 23.00.02 «Політичні інститути та процеси». – Національний університет «Одеська юридична академія», Одеса, 2019. У дисертації представлений комплексний аналіз категорії толерантності в різні історичні періоди. Визначені передумови та проблемні аспекти формування толерантності як політичного та політико-правового інституту. Відзначено перспективи розвитку інституту політичної толерантності в аспекті демократичного державотворення. Окреслено, що інституціоналізація та раціоналізація форм політичної взаємодії та політичної конкуренції представляють пріоритетні завдання інституту політичної толерантності. Обґрунтовано, що інститут толерантності забезпечує оновлення влади, та стимулює розвиток програм та концепцій розвитку держави. Відзначено, що політична толерантність як узгоджена система представництва інтересів різних політичних суб’єктів не виключає з політики критерій суперництва, а, навпаки, формує інституційні форми політичної боротьби та демократичні засади громадянської участі. А конформізм та радикалізм визначені як негативні тенденції сучасного соціально-політичного процесу, які стимулюють розвиток інтолерантних настроїв. Демократична парадигма політичних взаємин виступає основою творення відносин рівного партнерства політичного керівництва та політичної участі всіх інституцій громадянського суспільства та інших суб’єктів політичного процесу.

Диссертация на соискание научной степени кандидата политических наук по специальности 23.00.02 «Политические институты и процессы» – Национальный университет «Одесская юридическая академия», Одесса, 2019. В диссертационной работе представлен комплексный анализ интерпретаций категории толерантности, определены предпосылки и проблемные аспекты формирования толерантности как политического и политико-правового института. Проведены исследования проблемы общественно-управленческих отношений, институциональных моделей политического участия, политического коммуникативного дискурса, универсальных и специфических механизмов политической интеракции. Определено, что проблематика толерантности как демократического фактора, обеспечивающего свободу и альтернативность политического выбора и условия политической стабильности, остается актуальным вектором в современных научных исследованиях. Обосновано, что парадигма рационализации политического выбора и социальной открытости, представляет внутренние механизмы, формирующие политически толерантное общество. Проанализированы достижения зарубежного опыта в сфере государственно-политической, законотворческой и правоприменительной практики реализации института политической толерантности. Украинская практика демократического транзита, используя мировой опыт, должна учитывать существующие тенденции для создания собственной национальной модели института политической толерантности.

A thesis submitted for PhD (candidate of science) degree in political science, specialty 23.00.02 – Political institutions and processes. – National University «Odesa Law Academy», Odesa, 2019. The thesis presents a complex analysis of the category of tolerance through different historical periods, defines preconditions and problematic aspects of the formation of tolerance as a political and politico-judicial institution. The majority of modern studies are aimed at revealing models and mechanisms of socio-political interaction and principles of stable political process. Scientific explorations are aimed directly at finding conditions of implementation and functioning of the institution of political tolerance relevant for Ukrainian sociopolitical system, taking into account the practical experience of other countries in the field of implementation of the principles of tolerance. Some problems still exist, such as the absence of universal definitional apparatus of tolerance and dichotomous division of discursive meaning of tolerance as an active and conformal formation. It is determined that the institution of political tolerance has special meaning for democratic state-building. Thus, implementation of the institution of tolerance as a strategic landmark of state policy in the sphere of democratic transformations both on the regional and nation-wide level is an important condition for the process of democratization of political system. Comparative analysis of fundamental approaches towards the determination of the functional characteristic of tolerance as an action or inaction is conducted. The definitions are provided for fundamental categorical components of the institution of political tolerance for wider illustration of the main problems of research in the context of democratic coexistence of modern societies. It is justified, that political pluralism as a fundamental principle of the institution of tolerance, first of all, represents a platform of political innovations and initiatives, condition for the openness of political process for new participants and, simultaneously, works as a mechanism of development of active political opposition, alternative political courses. It is determined that political tolerance as a coordinated system of representation of interests for different political subjects, does not deprive politics of the criterion of competition, but, on the contrary, creates institutional forms of political struggle and democratic principles of civil participation. The author defines that critical states of political system, which manifest themselves during crisis of legitimacy of power, political elite, opposition, civil society and state institutions, evoke the phenomenon of political intolerance both on the level of social relations and on the level of state power, official representatives of the state, political leaders and other state and political structures. Impact of the media on the formation of intolerant attitudes within society is described. Coverage of certain topics on relations between political subjects in power, public demonstration of intolerant positions, intolerant public speeches, radical political programs and statements of official state subjects, statist and political radicalism become a platform for the projection of public intolerance on the model of political interactions between electoral parts. The author defines that political power which acts upon recognition of common meaningfulness of democratic rights and liberties and transparency of political decision-making, as well as the engagement of society in the political process, emerges as one of the main conditions for the creation of practices of political tolerance. It is noted that implementation of political tolerance as an institution in modern Ukrainian realities is possible within the framework of the complex transformation of social, state and political model of political participation. The thesis represents justification of important achievements of international experience in the sphere of state policy, law-making and law implementation practices (with states of the European Union and the USA as examples). Analysis of normative and legal base, law-making and political initiatives in the improvement of effective principles of development of tolerance as a political institution is conducted. Taking into account global experience, Ukrainian practice of democratic transition should pay attention to existing factors, which create negative tendencies, for the effective functioning of Ukraine’s national model of the institution of political tolerance
дис. ... канд. політ. наук : 23.00.02
Іванова А. В. Політична толерантність як імператив процесу забезпечення соціально-політичної стабільності: автореф. дис. ... канд. політ. наук : 23.00.02 / А. В. Іванова ; Нац. ун-т "Одеська юридична академія". - Одеса, 2019. - 17 с.
Keywords: інститут політичної толерантності; інтолерантність; демократичний транзит; політичний процес; політична стабільність; институт политической толерантности; интолерантность; демократический транзит; политический процесс; политическая стабильность; institution of tolerance; intolerance; democratic transition; political process; political stability